2013
DOI: 10.1021/tx400229e
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Polychlorinated Biphenyls by Liver Tissue Slices from Phenobarbital-Pretreated Mice Is Congener-Specific and Atropselective

Abstract: Mouse models are powerful tools to study the developmental neurotoxicity of polychlorinated biphenyls (PCBs); however, studies of the oxidation of chiral PCB congeners to potentially neurotoxic hydroxylated metabolites (OH-PCBs) in mice have not been reported. Here we investigate the atropselective oxidation of chiral PCB 91 (2,2',3,4',6-pentachlorobiphenyl), PCB 95 (2,2',3,5',6-pentachlorobiphenyl), PCB 132 (2,2',3,3',4,6'-hexachlorobiphenyl), PCB 136 (2,2',3,3',6,6'-hexachlorobiphenyl) and PCB 149 (2,2',3,4'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
86
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 40 publications
(94 citation statements)
references
References 61 publications
8
86
0
Order By: Relevance
“…A convenient nomenclature for PCB metabolites has been proposed by Maervoet et al and, as shown for PCB 136 in Fig 3, will be used throughout this manuscript (Maervoet et al 2004). The oxidation of C-PCBs, in particular those with a 2,3,6-trichloro substitution pattern in one phenyl ring, to HO-PCBs has been studied extensively using recombinant enzymes (Lu et al 2013, Lu and Wong 2011, Waller et al 1999, Warner et al 2009), hepatic microsomes (Kania-Korwel et al 2011, Kania-Korwel and Lehmler 2013, Schnellmann et al 1983, Wu et al 2014, Wu et al 2011), isolated hepatocytes (Vickers et al 1986) and, liver, hippocampus and skin slices (Garner et al 2006, Wu et al 2013a, Wu et al 2013b) obtained from mammalian species. To the best of our knowledge, the oxidation of C-PCBs in non-mammalian species, such as amphibians, fish or avian species, has not been investigated to date.…”
Section: Metabolism Of C-pcbs To Ho-pcbsmentioning
confidence: 99%
See 4 more Smart Citations
“…A convenient nomenclature for PCB metabolites has been proposed by Maervoet et al and, as shown for PCB 136 in Fig 3, will be used throughout this manuscript (Maervoet et al 2004). The oxidation of C-PCBs, in particular those with a 2,3,6-trichloro substitution pattern in one phenyl ring, to HO-PCBs has been studied extensively using recombinant enzymes (Lu et al 2013, Lu and Wong 2011, Waller et al 1999, Warner et al 2009), hepatic microsomes (Kania-Korwel et al 2011, Kania-Korwel and Lehmler 2013, Schnellmann et al 1983, Wu et al 2014, Wu et al 2011), isolated hepatocytes (Vickers et al 1986) and, liver, hippocampus and skin slices (Garner et al 2006, Wu et al 2013a, Wu et al 2013b) obtained from mammalian species. To the best of our knowledge, the oxidation of C-PCBs in non-mammalian species, such as amphibians, fish or avian species, has not been investigated to date.…”
Section: Metabolism Of C-pcbs To Ho-pcbsmentioning
confidence: 99%
“…The 4,5-epoxide intermediate of C-PCBs with a 2,3,6-trichloro substitution pattern can rearrange to form both 4- or 5-hydroxylated PCB metabolites. In addition, a 1,2-shift (or NIH-shift) (Guroff et al 1967, Jerina and Daly 1974) of the 3-chloro substituent can lead to the formation of HO-PCBs with a 2,4,6-trichloro-3-hydroxy substitution pattern as minor metabolites (Kania-Korwel et al 2012, Kania-Korwel et al 2011, Wu et al 2013a, Wu et al 2014). Studies with recombinant P450 enzymes demonstrate that CYP2B isoforms, such as rat CYP2B1 (Lu et al 2013, Waller et al 1999, Warner et al 2009), human CYP2B6 (Warner et al.…”
Section: Metabolism Of C-pcbs To Ho-pcbsmentioning
confidence: 99%
See 3 more Smart Citations